Factors Influencing Students’ Choice of Accounting as a Major: The Case of Botswana Accounting Students - Wally-DIMA, Lillian B (Asian Journal of Empirical Research, 2013)
This study examines the factors that have influenced students at the University of Botswana to select accounting as a major and to establish at what stage the decision was made. There is need for renewed research to examine how students perceive accounting as a major especially given the challenges that the accountancy profession has been faced with over the past decade. Data was collected from final year accounting students at the University of Botswana who were majoring in accounting using a questionnaire. The finding suggests that the major factors influencing students to take accounting include availability of advancement opportunities, personal interest in the subject, availability of employment after graduation, passion for the profession and high earnings compared with other professions. The finding also revealed that majority of the students made the choice to major in accounting after high school but before entering the university and about a third of the respondents made the decision at high school.